Front-feedback-based two-stage switch architecture - SHEN Zhi-jun; ZENG Hua-shen; XIA Yu (Tongxin xuebao)
To relax the time constraint of the FTSA（feedback-based two-stage switch architecture）,a new scheme called FFTS（front-feedback-based two-stage switch architecture） was proposed,which enabled the cell transmission to take place in parallel with the scheduling process with the adoption of putting the feedback operation before the cell transmission and thus extended the time space of the scheduling algorithm effectively.In addition,the FFTS used the double-cell-buffer mode and re-sequencing buffer to solve the consequent problem such as cell conflict and disordering.Simulation and analysis show that FFTS has a better delay performance compared with the other non-feedback two-stage switch architecture.